2019
DOI: 10.1242/dev.170589
|View full text |Cite
|
Sign up to set email alerts
|

A chemical-genetics approach to study the role of atypical protein kinase C in Drosophila

Abstract: Studying the function of proteins using genetics in cycling cells is complicated by the fact that there is often a delay between gene inactivation and the time point of phenotypic analysis. This is particularly true when studying kinases that have pleiotropic functions and multiple substrates. Drosophila neuroblasts (NBs) are rapidly dividing stem cells and an important model system for the study of cell polarity. Mutations in multiple kinases cause NB polarity defects, but their precise functions at particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 66 publications
(106 reference statements)
3
35
0
Order By: Relevance
“…Long-term disruption of aPKC activity enables constitutive binding of unphosphorylated Lgl at the plasma membrane, which could mask a role for Dlg in Lgl cortical recruitment. We therefore inactivated aPKC acutely using a recent analogue-sensitive aPKC allele (Hannaford et al, 2019). Live imaging of endogenously expressed Lgl-GFP shows that aPKC inhibition induces a quick reallocation of Lgl from the cytoplasm to the cortex in dlg mutant cells ( Figure 3H).…”
Section: Dlg/scrib Regulate Lgl Dynamics and Localization By Preventimentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term disruption of aPKC activity enables constitutive binding of unphosphorylated Lgl at the plasma membrane, which could mask a role for Dlg in Lgl cortical recruitment. We therefore inactivated aPKC acutely using a recent analogue-sensitive aPKC allele (Hannaford et al, 2019). Live imaging of endogenously expressed Lgl-GFP shows that aPKC inhibition induces a quick reallocation of Lgl from the cytoplasm to the cortex in dlg mutant cells ( Figure 3H).…”
Section: Dlg/scrib Regulate Lgl Dynamics and Localization By Preventimentioning
confidence: 99%
“…UAS-Lgl 3A -GFP and UAS-Lgl-GFP (Betschinger et al, 2003) for overexpression conditions; (Betschinger et al, 2003); aPKC K06403 (Wodarz et al, 2000); apkc as4 , an analogue-sensitive allele used for acute inhibition of aPKC (Hannaford et al, 2019, kindly provided by Jens Januschke); scrib 2 . We used a recently generated dlg 1A mutant allele, which was produced with low concentrations of ethyl methylsulphonate to diminish secondary alterations Yamamoto et al, 2014).…”
Section: Drosophila Stocks and Geneticsmentioning
confidence: 99%
“…Recent studies have revealed that the phosphorylation state of Mira is important for cortical localisation [22]. During interphase, Mira is non-phosphorylated and is uniformly associated with the plasma membrane, but aPKC-mediated phosphorylation at metaphase prevents the localisation of Mira at the apical pole [22,23]. Furthermore, the asymmetric localisation of Mira is maintained through interactions with its cognate mRNA [24].…”
Section: Neural Lineages As the Source Of Tumoursmentioning
confidence: 99%
“…Thus, the exquisite regulation of spatial (apical) aPKC activity in the cortex is critical for the establishment of neural stem cell versus progenitor identity, in part through the asymmetric segregation of Numb [81]. Another study generated an analog-sensitive mutant of DaPKC [82]. Analog-sensitive mutants substitute a structurally conserved bulky amino acid such as methionine, leucine, phenylalanine or threonine in the active site of kinases termed as 'gatekeeper residue' to a residue with a much smaller side chain [83].…”
Section: Apkc Polarity and Neuronal Differentiationmentioning
confidence: 99%
“…This enables binding of kinase inhibitors with large bulky groups, such as C3-tolyl ring, specifically to the engineered kinase while sparing wild-type kinases [83]. Employing the analog-sensitive DaPKC mutants, the authors were able to demonstrate that acute inhibition of DaPKC during neuroblast polarity establishment abolished the asymmetric localization of Miranda, as well as Numb, while PARD3 and DLG (discs large) were mostly unaffected [82].…”
Section: Apkc Polarity and Neuronal Differentiationmentioning
confidence: 99%